Construction of Public Opinion in Online News on the Issue of Nurses’ Expulsion from Boarding House: A Critical Discourse Analysis - Octavia Chandra Dewi; Rosaria Mita Amalia (TEKNOSASTIK, 2021)
In the pandemic of covid-19 that has spread worldwide, health workers become heroes that stand on the frontline of the battle to fight the coronavirus, and ‘public enemies’ as well, they are also the people who interact directly with the virus through their patients. The case of nurses’ expulsion from boarding house, has proved that society around them is afraid of being contaminated by the virus through their interaction with health workers. This study was conducted using Critical Discourse Analysis study (CDA) through the three dimensions by Van Dijk (1997) upon the texts to describe and to analyze the social actors involved in the case of nurses’ expulsion from boarding house along with their roles in constructing public opinion through online news; to describe and to analyze the forms of power abuses and social inequality used by the social actors involved in this case which construct public opinions. The object of the study is taken from online article about a review about the nurses’ expulsion from boarding house in Solo, central Java, in pikiran-rakyat.com. The source of data analysis was the text of the review itself, and the public comments about the issue. The analysis upon the social actors’ attitudes and utterances, including the public’s comment about the issue showed that the bad person can be the victim as well, depends on the construction upon public opinion.